2022
DOI: 10.1371/journal.pone.0262852
|View full text |Cite
|
Sign up to set email alerts
|

“Post-GDM support would be really good for mothers”: A qualitative interview study exploring how to support a healthy diet and physical activity after gestational diabetes

Abstract: Background Women with a history of gestational diabetes mellitus (GDM) are at high risk of developing type 2 diabetes mellitus (T2DM). They are therefore recommended to follow a healthy diet and be physically active in order to reduce that risk. However, achieving and maintaining these behaviours in the postpartum period is challenging. This study sought to explore women’s views on suggested practical approaches to achieve and maintain a healthy diet and physical activity to reduce T2DM risk. Methods Semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Unlike pharmacological interventions that cease when the intervention ends (that is, treatment is removed), lifestyle interventions may lead to changes in diet and physical activity that can be maintained after the study. Although the postpartum period may be a more appropriate time to learn and establish new routines, 12,39 and previous reviews have highlighted greater effectiveness for interventions that start after delivery, 18,19 this may explain why we did not observe significant differences according to timing relative to pregnancy. Prompted by recommendations based on a qualitative synthesis, we have previously identified a wide range of intervention elements that may help to support women to reduce their T2DM risk by making changes to their diet and physical activity 12 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Unlike pharmacological interventions that cease when the intervention ends (that is, treatment is removed), lifestyle interventions may lead to changes in diet and physical activity that can be maintained after the study. Although the postpartum period may be a more appropriate time to learn and establish new routines, 12,39 and previous reviews have highlighted greater effectiveness for interventions that start after delivery, 18,19 this may explain why we did not observe significant differences according to timing relative to pregnancy. Prompted by recommendations based on a qualitative synthesis, we have previously identified a wide range of intervention elements that may help to support women to reduce their T2DM risk by making changes to their diet and physical activity 12 .…”
Section: Discussionmentioning
confidence: 63%
“…Women with GDM are encouraged to maintain healthy lifestyles during and after pregnancy, in particular to establish a healthy BMI through being physically active and eating healthily. However, most women exhibit discordant T2DM risk perception and behaviour, and need more support to achieve and sustain such changes 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, as we have shown in the present study, spouses with a high level of health awareness often accompany women and encourage them to do physical exercise, which is regarded as a strong incentive to achieve a healthy lifestyle [ 38 ]. In addition, peers can build a mutual aid system by sharing experiences and motivating one another [ 43 ], which empowers patients with diabetes to improve their self-efficacy [ 44 ]. In the present study, some women suggested the setting up of a WeChat group to share knowledge and skills regarding diabetes, based on their own personal experiences, a finding that was also made in another qualitative study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peers can build a mutual aid system by sharing experiences and motivating one another [ 43 ], which empowers patients with diabetes to improve their self-efficacy [ 44 ]. In the present study, some women suggested the setting up of a WeChat group to share knowledge and skills regarding diabetes, based on their own personal experiences, a finding that was also made in another qualitative study [ 43 ]. This provides a reference for us to formulate more targeted and effective strategies to assist this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Further, consistent engagement of midwives with woman's significant others, including family members, a partner, friends or colleagues, and involving them in counselling, education and feedback during the management process needs to be considered. The involvement of relatives was mentioned by other researchers as a source of support and complimentary care from significant others has been reported to be sought by women diagnosed with GDM [ 43 , 44 ]. Social support in the management of GDM was identified as crucial for effective glycaemic control [ 45 ].…”
Section: Discussionmentioning
confidence: 99%